From the Strawberry to the Snowflake to Nuclear Democracy - Gagnon, Jean-Paul (Theoria (Pietermaritzburg), 2025)
Indigenous research frameworks, such as heart-led practices from the Anishinaabe and Ojibwe perspectives, demonstrate how theory can be derived from the place and purpose of a real, non-human, entity or event. This article develops theory for democracy out of snow – both in terms of how it manifests and what happens when it falls over where people live. From this snow-led intervention into democratic theory comes the argument that democratic moments, like elections, mini-publics, snow and protests, should be critically engaged for the ways in which they can generate sporadic events and for how they can relax or harden every-day social, political, economic, and legal structures which can lead to democratic possibilities. When snow falls to earth, especially in large volume, it temporarily presents itself to people who must interact with it and these people can, by consequence, become temporarily democratized by relation.